Dealloying-based metal-polymer composites for biomedical applications. (15th March 2018) - Okulov, A.V.; Volegov, A.S.; Weissmüller, J.; Markmann, J.; Okulov, I.V.
Abstract: Here, we developed interpenetrating-phase metal-polymer composites mimicking mechanical behavior of cortical bone and occupying previously unclaimed region at the Ashby diagram in the area of intermediate strength and low stiffness. The composites consist of dealloying-based open porous Tix Hf100 − x alloys (scaffolds) impregnated by polymer. The scaffolds significantly contribute to strength (215–266 MPa) and stiffness (15.6–20.8 GPa) of the composites while the polymer phase provides their high strain rate sensitivity (0.037–0.044). Tuning scaffolds' connectivity by preloading and/or their chemical composition allows fine optimization of composites' mechanical properties. The results suggest that the composites may provide a basis for promising future implant materials. Graphical abstract: Image 1